biological activity of Ammodaucus leucotrichus Coss. & Dur. collected from Oued Souf region - DJEDIDI Safa; DERKI Manar El Ones (Université of Eloued, 2024)
This study investigates the effectiveness of flavonoids (Diethyl ether, ethyl acetate, butanol and aqueous fractions) from the Oum Diriga plant (Ammodaucus leucotrichus Coss. & Dur.) collected from Oued Souf region as an intidepression, analgesic, antioxidant and antiinflammatory activities. In intidepression tests, we studied through In Vivo tests that include two main tests. The first is the tail suspension test, and the second is the forced swim test. The Diethyl ether and butanol extracts (40 mg/mL) showed a more effective than the positive control, where the duration of immobility was estimated at 10 seconds. In addition, diethyl ether extract (40 mg/ml) and in ethyl acetate extract (20 mg/ml) showed effectiveness in relieving pain. Based on the results of the hot plate test and the writhing test, the duration of pain tolerance were estimated as 26 seconds in hot plat test, while the percentage of inhibition was recorded as 84.55% in Writhing test at butanol extracts at a concentration of 40 mg/mL. In vitro the Antioxidant, anti-inflammatory activities, the ethyl acetate extract showed significant antioxidant activity in the DPPH and FRAP tests, where the results were very close to the ascorbic acid standards, with an IC50 value of 0.06 mg/mL and an EC50 value of about 0.0352 mg/mL. In the total antioxidant capacity test, the diethyl ether extract showed the highest value with the average estimated at (11 mg E As A\mg Ex) In the hemolysis test, the best IC50 value of the ethyl acetate extract estimated at 0.38 mg/mL. In addition, the Ethyl Acetate extract has proven to be a high sun protection factor estimated 145. As for the anti-inflammatory activity through egg albumen denaturation test, the Butanol extract it showed an effectiveness of IC50 estimate of 0.18 mg/mL
Keywords: Ammodaucus leucotrichus Coss. & Dur.; Flavonoids; Intidepression; Analgesic; Antioxidant activity; Anti-inflammatory activity.